Repositório digital para o patrimônio arquivístico documental: subsídio para acesso e preservação do diário de classe - Lampert, Sérgio Renato (2013)
This research addresses issues related to the implications of the implementation of a digital repository for the digital diary of class of Centro Universitário Franciscano, member of archival documental heritage of the institution, and his involvement with the principles and concepts of archival science and digital preservation. The Diary of class is the document that contains the information concerning the registration of frequency, student assessment and ministered content, serving as a source of evidence of teacher activity. This study is justified by the understanding that the implementation of a digital repository, coupled with digital preservation initiatives, provides grants for access, storage and preservation of documentary heritage of UNIFRA. In this context, the purposes of this study consist in propose archival policies that permeate the lifecycle of class diary, set the diary class while record, implement a digital repository for class diary and define functional requirements for trusted digital archival repositories. It is understood that the research objectives are identified as guiding elements that intertwine and complement each other to evaluate the implementation of a digital repository, with a views the storage of the collection Institutional and to ensure access for long term. For both, carried out an applied research with a qualitative approach, exploratory, classified as bibliographic and case study. Data collection was obtained through book report bibliographic, observation, form and document analysis, and the data were analyzed using the theoretical framework of the research. The results of the study pointed for permanent custody destination to the Diary Class, the classification structure and temporality documental class related to production diary class. Similarly, we observed the generation a document with archival prerogatives, integrate and reliable, produced in format open standard presented in its manifested form, with stable content and fixed form. Furthermore, we obtained the implementation of a repository in accordance with the OAIS Reference Model. also, performed elaboration the document entitled "Recommendations for a trusted digital archival repositories for the digital class diary", identified as result product of the Professional Masters. This document presents requirements and core technologies to preserve and store digital documents, as well as to ensure authenticity and access continued to digital objects stored. Finally, we conclude that any intervention to be made into digital documents, must imperatively be preceded by archival policies to ensure access for long-term archival documental heritage.